The Obstacles of promoting Cambodian currency a cross country comparative study - KHORN, Dalin (KDI School, 2016)
Hysteresis has caused Cambodia to be a highly dollarized country, yet implemented policies have failed to fully promote Cambodian currency. This research is seeking to identify the reasons behind these obstacles and propose policy recommendations for promoting Cambodian currency. To reach the research objective, time series analysis, existed literatures, and cross country comparison were employed in this paper. The main finding is that there are inconsistent government policies between promoting the Riel and attracting capital inflows. In addition, the market-development prudential policy implementation is limited and capital market is immature comparing to other countries. Hence, maintaining the macroeconomic condition is significant, and two important areas to promote national currency are capital financial market development, and accumulative and marketable prudential policies by giving more incentive to the Riel users. Moreover, minimizing the conflicting policies are also key contribution to promote the Riel.
Thesis(Master) --KDI School:Master of Development Policy,2016